Model of classification system of tool wear condition while machining by turning - Antić, Aco; Hodolič, Janko; Zeljković, Milan; Živković, Aleksandar (Journal of Production Engineering, 2009)
This work deals with a model of a developed fuzzy system for tool wear classification. The system consists of three modules: module for acquisition and data processing, for tool wear classifying and for decision making. In addition, some of the methods of signal processing used for defining the entering fuzzy classifier vector have been given.